Flexible syntheses of 5, 8-disubstituted indolizidine poisonous-frog alkaloids via a Michael-type conjugate addition. (1st February 2017) - Zhou, De-Jun; Wang, Zhen-Hui; Zhang, Yan-Ru; Cui, Zheng-Guo
The efficient and flexible syntheses of 5, 8-disubstituted indolizidine poisonous-frog alkaloids is described using a highly stereoselective Michael-type conjugate addition reaction as the key step. In this work, syntheses of the 5, 8-disubstituted indolizidine poisonous-frog alkaloids (–)-231C, (–)-221I and the proposed structure for (–)-193E are reported.